Essential fatty acid and analysis of their impact on the human body based on latest research - Taborska, Nina; Martyka, Anna; Kubicka-Figiel, Martyna; Ujma, Przemysław (Journal of Education, Health and Sport, 2024)
Introduction Fats contained in food are the most concentrated source of energy, fat-soluble vitamins and essential polyunsaturated fatty acids (EFA). Of the four types of unsaturated acids, three main families have specific biological effects: omega-3, omega-6 and omega-9. Objective of the work The aim of the study was to review the current knowledge about the action and consumption of products rich in EFAs and to present the topic of conscious supplementation with "fashionable" omega acids. Materials and methodology A literature selection was performed from the PubMed and Google Scholar databases. Articles were searched in English and Polish. Results Most research indicates the beneficial effect of omega acids on the human body. The recommended daily intake of omega fatty acids is a maximum of 3 grams. EFAs have a versatile effect - they have anti-inflammatory and lipid-lowering effects, and support our cardiovascular and autoimmune systems. They have a positive effect on the intestinal microflora and our skin. Conclusions Consumption of products rich in omega acids and their appropriate supplementation bring many health benefits. Nevertheless, the assessment of the effectiveness and safety of the use of polyunsaturated fatty acids in the treatment of various diseases requires further detailed research.